Assessment of Self Regulated Learning Strategy Using Motivated Strategies for Learning Questionnaire in Anatomy Course Among Undergraduate Medical Students in Bangladesh - Mostafa, Asma (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: 'Self-Regulated Learning (SRL)' means one’s ability to organize and control their learning environment. Self regulated learners develop a deep understanding of subject matter which positively influences academic performance. On this basis, the present study is aimed to assess student’s anatomical 'SRL' strategies and to investigate whether anatomical 'SRL' can predict academic performance in Anatomy course. Methods: This was a cross-sectional study. The study group consisted of a convenient sample of 105 first year undergraduate medical students of Bangladesh who were learning Anatomy for last 6 months. The 'Motivated Strategies for Learning Questionnaire' was used. Information regarding age, gender, medium they were studying prior entering into M.B.B.S course and their anatomy result was collected. Data were analyzed using SPSS version 19. Results: The present data suggests that the study group was sufficiently motivated for learning in Anatomy as measured by intrinsic goal orientation, task value and self-efficacy of learning and performance. It also demonstrates that students who were more likely to use learning strategies such as rehearsal, elaboration, organization, peer learning and help seeking had higher levels of academic performance. Female students and those from Bangla medium reported more effective study habits. Conclusion: These results indicate that adopting SRL strategics are likely linked to Anatomy performance. Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 10-13